Delayed puberty in thalassemia major patients - Jose RL Batubara; Arwin Akib; Diah Pramita (Paediatrica Indonesiana, 2004)
Background Delayed puberty is the most common endocrine com-plication in thalassemia major. The main cause of delayed pu-berty in thalassemia major is the failure of the hypothalamic-pitu-itary axis due to iron accumulation in the pituitary.Objectives The purpose of this study was to determine the preva-lence of delayed puberty in Î²-thalassemia major patients in theDepartment of Child Health, Cipto Mangunkusumo Hospital,Jakarta. This study also evaluated the adequacy of chelationtherapy and determined serum gonadotropin and sex hormonelevels in these patients.Methods Seventy-two patients with Î²-thalassemia major aged 13-18 years old who visited the Thalassemia Outpatient Clinic of CiptoMangunkusumo Hospital during February-July 2003 were includedin the study. Each subject underwent examinations to determinethe body weight and height, pubertal status, serum iron level, totaliron binding capacity, and the levels of serum LH, FSH, estradiol(in girls) or testosterone (in boys).Results Delayed puberty occurred in 40 of 72 patients (56%). Themajority of patients with delayed puberty showed low levels of se-rum LH, estradiol, and testosterone whereas low levels of serumFSH only occurred in 6 of 21 boys and 11 of 19 girls. Most of thepatients without delayed puberty had normal levels of serum LH,FSH, and estradiol, but 8 of 16 boys showed decreased serumtestosterone levels. Only 3 patients used chelation therapy ad-equately, all of them showed normal puberty.Conclusions The prevalence of delayed puberty in Î²-thalassemiamajor patients in this study was still high (56%). Periodic examina-tion and recording of pubertal stage need to be done in girls whohave reached 8 years old and boys who have reached 9 years oldso that early detection and management of delayed puberty canbe done.